DEVELOPMENTAL INDIVIDUAL-DIFFERENCES RELATIONSHIP-BASED (DIR) FLOORTIME DALAM MENINGKATKAN KOMUNIKASI DUA ARAH PADA KASUS AUTISM SPECTRUM DISORDER (ASD) - Stella Rosalina Phandinata; Ediastri Toto Atmodiwirjo; Debora Basaria (Universitas Bunda Mulia, 2017)
Autism Spectrum Disorder (ASD) is a developmental disorder that has communication disorders as its characteristic. Greenspan introduced the DIR Floortime model which is proven to be able to improve the communication circles of ASD child and teens. This study aims to see the role of DIR Floortime in improving two-way communication of adolescent with ASD. With single-subject experimental design, this study consisted of 10 pre-intervention sessions, 20 intervention sessions and 10 post-intervention sessions, 2 sessions in 1 day with 20 minutes duration. Two-way communication capability is measured using Functional Assessment Scale and number of communication circles during the session. Based on an assessment of JW, a 14-year-old teenager with Autism Spectrum Disorder, it is found: JW has a dominant sensory-seeking in the tactile and auditory areas. JW mental age is equal to 6 year-old child. JW has reached the third development milestone, two-way purposeful communication, but JW is not optimal yet in this milestone. From the results, the DIR Floortime is able to improve two-way purposeful communication significantly in adolescent with Autism Spectrum Disorder. In addition, DIR Floortime is also able to increase circles of communication significantly in adolescent with Autism Spectrum Disorder. Specifically, there is an increase in the quantity and also improvement in the quality of opening the communication circles. While the ability to close the communication circles is only improved in quality. JW is able to respond the researcher with series of behavior after the DIR Floortime intervention is given.Keywords: DIT Floortime, two-way communication, circle of communication, autism spectrum disorder, adolescent